A qualitative study exploring depressed participants’ experiences of receiving Augmented Depression Therapy (ADepT) - Rebecca Watson; Kim A Wright; Nigel Reed; Barney Dunn; Emily Widnall; Kalliopi Demetriou; Laura Warbrick; Katie Marchant; Nicole Geschwind; Isabella Magner-Parsons; Rachel Barter (BMJ Open)
Objectives The current study aimed to explore participants’ views on the acceptability, impact and mechanisms of change of Augmented Depression Therapy (ADepT), a novel wellbeing-focused and recovery-oriented psychological therapy for depression.Design A semi-structured qualitative interview design was used, with data analysed using the framework approach.Participants 20 participants with anhedonic depression who had received up to 20 sessions of ADepT, sampled from a pilot randomised controlled trial of ADepT versus Cognitive Behavioural Therapy (CBT).Setting A primary care psychological therapy clinic in Devon, UK, with interviews occurring between May 2018 and February 2020.Results Participants found the wellbeing focus of ADepT acceptable. Helpful aspects of therapy were a positive therapeutic bond, the structure and flow of therapy scaffolding the learning journey, the tools and techniques of therapy helping building wellbeing and booster sessions supporting long-term recovery. Negative aspects for some participants were therapy feeling too intense and triggering feelings of failure. Participants reported significant positive impacts of treatment on wellbeing, functioning and hope. Perceived mechanisms of change were reorienting to the positive, engaging with valued goals, taking a proactive life stance, gaining confidence and motivation for change, breaking down tasks into small steps, cultivating self-care and self-compassion, enhancing help seeking and interpersonal effectiveness, changing the relationship to depression, and rediscovering the self beyond depression.Conclusions Findings suggest that the wellbeing focus of ADepT is acceptable and leads to positive impacts, supports the logic model underpinning the intervention, and warrants continuation to a definitive trial.Trial registration number ISRCTN85278228.